Turbulent Shear Flows I 1979
DOI: 10.1007/978-3-642-46395-2_6
|View full text |Cite
|
Sign up to set email alerts
|

The Calculation of Three-Dimensional Turbulent Free Jets

Abstract: The paper presents an application of the two-equation k-e model to the problem of three-dimensional free jets issuing from rectangular orifices. The turbulence model has been modified so that plane and round jets may be predicted with the same empirical input. The continuity, momentum, and turbulence equations are solved using the fmite difference procedure of Patankar and Spalding for three-dimensional parabolic flows and results are presented for aspect ratios of 1,5,10, and 20. The decay of axial velocity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 13 publications
(23 reference statements)
1
37
1
Order By: Relevance
“…In order to fix this deficiency, some modifications for the model constants of the dissipation equation have been proposed as described in detail in [3]. In several modifications, the constants C 1 and C 2 (the constants in the dissipation equation) are made as a simple or complicated function of the velocity decay rate and jet width [18,23]. However despite a number of complicated modifications, Dally et al [3] have shown that, with the use of constant value of C 1 = 1.6 instead of the standard value of 1.44 a very significant improvement was obtained in the calculation results for the round jets, better than any other complicated modifications (for convenience here we denote this modification of LRR-IP model as BM-M1, for "basic model modification 1").…”
Section: Modification Of the Lrr-ip Model For The Bluff-body Flowmentioning
confidence: 99%
“…In order to fix this deficiency, some modifications for the model constants of the dissipation equation have been proposed as described in detail in [3]. In several modifications, the constants C 1 and C 2 (the constants in the dissipation equation) are made as a simple or complicated function of the velocity decay rate and jet width [18,23]. However despite a number of complicated modifications, Dally et al [3] have shown that, with the use of constant value of C 1 = 1.6 instead of the standard value of 1.44 a very significant improvement was obtained in the calculation results for the round jets, better than any other complicated modifications (for convenience here we denote this modification of LRR-IP model as BM-M1, for "basic model modification 1").…”
Section: Modification Of the Lrr-ip Model For The Bluff-body Flowmentioning
confidence: 99%
“…Properties for jets that are not issuing from circular cross-section apertures are not so well documented due to the smaller number of studies of such jets [1]. Simulations of this type of jet using computational uid dynamics (CFD) have also appeared to be di cult [2]. One example where these jets are present is in the o shore oil and gas industry.…”
Section: Introductionmentioning
confidence: 99%
“…Boundary conditions for both cases are selected such that boundaries except nozzle exit and nozzle wall have zero gradients for pressure and velocity [24]. In addition, the choked nozzle exit plane has pressure, temperature, velocity, and flow angle specified as: …”
Section: Boundary Conditionsmentioning
confidence: 99%